Mutation of histidine 286 of the human P2X(4) purinoceptor removes extracellular pH sensitivity - Clarke, C E (Blackwell Science Inc, 2000)
1. Effects of external pH on the human P2X(4) purinoceptor, an ATP-activated ion channel, were studied using the Xenopus oocyte expression system. 2. Changing the external pH from 7·4 to 6·5 significantly reduced, whilst an increase to pH 8 enhanced, maximum ATP-activated current amplitude, without changing the current- voltage relationship of the ATP-activated current. 3. Diethyl pyrocarbonate (DEPC; 10 mM) treatment of P2X(4)-injected oocytes had no effect on the pH sensitivity of the ATP-activated current. 4. Site-directed mutagenesis of histidine 286 (H286) to alanine completely abolished the pH sensitivity of the P2X(4) receptor at all agonist concentrations. ATP potency showed a small (fourfold) leftward shift. Mutagenesis of the other three histidines present in the P2X(4) sequence had no effect on pH sensitivity. 5. The results show that pH modulation of P2X(4) in the pathophysiological range is mediated by protonation of H286. This provides direct confirmation that pH sensitivity resides in the P2X(4) channel protein rather than the agonist species.